2017
DOI: 10.1111/hae.13279
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of haemophilia B: A critical appraisal of the evidence and current practices

Abstract: The literature review revealed that documented experience in the perioperative management of bleeding risk in haemophilia B patients is relatively scarce. Therefore, the review was amended to provide a comprehensive overview of the perioperative management for haemophilia A and B patients; the expert panel applied a particular focus to haemophilia B. Several gaps were identified in the literature including the lack of consensus on defining surgery in terms of bleeding risk, optimal factor levels during surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 58 publications
(92 reference statements)
0
19
0
Order By: Relevance
“…Only a few decades ago, surgery in hemophiliacs was considered difficult and was associated with significant risks, such as uncontrolled bleeding, hemolytic complications associated with impure factor concentrates, transmission of bloodborne infections, and problems with wound healing [8,9]. With advancements in the treatment of hemophilia and the ability to replete deficient factor levels, surgery can be performed more safely.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few decades ago, surgery in hemophiliacs was considered difficult and was associated with significant risks, such as uncontrolled bleeding, hemolytic complications associated with impure factor concentrates, transmission of bloodborne infections, and problems with wound healing [8,9]. With advancements in the treatment of hemophilia and the ability to replete deficient factor levels, surgery can be performed more safely.…”
Section: Discussionmentioning
confidence: 99%
“…An international multi‐center observational cohort study was performed in which data were collected from 118 severe and moderate hemophilia B patients from five Hemophilia Treatment Centers in the Netherlands and five in the United Kingdom. Patients of all ages, who had undergone a minor or major elective surgical procedure between 1 January 2000 and 1 December 2015, were included . Details of the study data have been reported previously .…”
Section: Methodsmentioning
confidence: 99%
“…The risk of surgery-related bleeding has been reduced by standard FIX products, but comparisons with nonacog beta pegol or EHL products in the perioperative setting are limited by the relative scarcity of literature on bleeding risks in patients with hemophilia B. 31 34 Moreover, there is great variability in defining bleeding risk and a lack of robust evidence on surgical outcomes. 34 Nevertheless, perioperative use of nonacog beta pegol requires lower consumption and fewer injections than that reported for standard FIX products.…”
Section: Clinical Efficacy Of Glycopegylated Rfixmentioning
confidence: 99%
“… 31 34 Moreover, there is great variability in defining bleeding risk and a lack of robust evidence on surgical outcomes. 34 Nevertheless, perioperative use of nonacog beta pegol requires lower consumption and fewer injections than that reported for standard FIX products. 23 …”
Section: Clinical Efficacy Of Glycopegylated Rfixmentioning
confidence: 99%